Safety and Efficacy of Inferior Vena Cava Reconstruction During Hepatic Resection. (September 2019) - Papamichail, M.; Marmagkiolis, K.; Pizanias, M.; Koutserimpas, C.; Heaton, N.
Background and Aims: Patients with liver tumors involving the inferior vena cava have a poor outcome without surgery. Liver resection en bloc with inferior vena cava resection and reconstruction is now performed in many centers. The purpose of this study is to investigate the safety and efficacy of inferior vena cava reconstruction during hepatic resection. Materials and Methods: A review of 12 centers reporting 240 patients with combined hepatectomy and inferior vena cava resection and reconstruction for malignant tumors was performed. Sample size, patient characteristics, histological type of the tumor, method of reconstruction, complications, and long-term survival (1-, 2-, and 5-year survival) were evaluated. Results: A total of 240 patients from 12 institutions (male 58%) with mean age 54 years underwent combined liver resection and inferior vena cava resection and reconstruction for colorectal liver metastases (43%), cholangiocarcinomas (26%), hepatocellular carcinomas (19%), leiomyosarcomas (4%), and other tumors (7.9%). Reconstruction included primary closure (35.8%), patch repair (13.3%), or interposition graft (50.8%) In-hospital mortality was 6.25% and overall morbidity was 42.1%. 1- and 10-year survival rates were 79.7% and 28.9%, respectively. Conclusion: Tumors arising in or extending to inferior vena cava that require liver resection should be considered for surgery as it can be performed with an acceptable mortality and morbidity in centers with liver transplantation and hepato-pancreato-biliary facilities.